2012
DOI: 10.4161/psb.21320
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular hydrogen peroxide, produced through a respiratory burst oxidase/superoxide dismutase pathway, directs ingrowth wall formation in epidermal transfer cells of Vicia faba cotyledons

Abstract: Nutrient partitioning within plants is primarily regulated at sites of intense apo-/symplasmic nutrient exchange such as loading/ unloading of vascular systems and loading of developing seeds.1 Space constraints at these sites necessitate high nutrient fluxes per transport cell thus creating potential "transport bottlenecks" by substrate saturation of their membrane transporters. A striking solution to this problem has been the evolution of a cell design where plasma membrane surface areas are substantially am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Extracellular ROS, produced by ethylene-induced respiratory burst oxidases (rbohs), regulate biosynthesis and polarized deposition of the uniform wall in epidermal TCs [ 6 , 32 ]. Similarly, rboh expression co-occurs with wall ingrowth formation in barley BETCs [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular ROS, produced by ethylene-induced respiratory burst oxidases (rbohs), regulate biosynthesis and polarized deposition of the uniform wall in epidermal TCs [ 6 , 32 ]. Similarly, rboh expression co-occurs with wall ingrowth formation in barley BETCs [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ROS-related gene expression was dominated by those involved in extra- and intracellular ROS homeostasis (Additional file 11 ) suggesting that ingrowth wall formation depends upon a spatio/temporal fine-tuning of ROS. For instance, antioxidant capacity could be down regulated by ascorbic acid oxidation catalyzed by an extracellular L-ascorbate oxidase ([ 33 ]; Additional file 11 ) whilst concurrent ROS degradation by peroxidation [ 32 ] could be mediated by carboxymethylenebutenolidase-like protein (Additional file 11 ), secreted to the cell wall [ 34 ]. In contrast to epidermal TCs, differentially expressed peroxidases were not detected in barley BETCs [ 8 ] and were strongly down-regulated in nematode giant TCs [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that early stages of reticulate ingrowth deposition can be highly localized to discrete regions within an individual PP TC, and then continued deposition causes consolidation of these patches into more continuous regions of ingrowth deposition. The signals directing such localized patches of ingrowth deposition are unknown, but in non-vascular TC types the reactive oxygen species hydrogen peroxide has been implicated as a polarizing signal directing wall ingrowth deposition [ 5 , 30 , 31 ]. Recently, localized plumes of Ca 2+ have been implicated in directing the highly localized deposition of individual papillae wall ingrowths in epidermal TCs of V. faba cotyledons [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Xia et al . () demonstrated that extracellular hydrogen peroxide directs ingrowth wall formation in epidermal transfer cells of Vicia faba cotyledons. Salt stress has been shown to reduce production of reactive oxygen species (ROS) in maize leaves (Rodríguez et al .…”
Section: Discussionmentioning
confidence: 99%